Inhibition of NMDARs in the nucleus reticularis of the thalamus produces delta frequency bursting - Zhang, Yuchun; Llinas, Rodolfo R.; Lisman, John (Frontiers in Neural Circuits, 2009)
Injection of NMDAR antagonist into the thalamus can produce delta frequency EEG oscillations in the thalamocortical system. It is surprising that an antagonist of an excitatory neurotransmitter should trigger such activity, and the mechanism is unknown. One hypothesis is that the antagonist blocks excitation of GABAergic cells, thus producing disinhibition. To test this hypothesis, we investigated the effect of NMDAR antagonist (APV) on cells of the nucleus reticularis (nRT) in rat brain slices, a thalamic nucleus that can serve as a pacemaker for thalamocortical delta oscillations and that is composed entirely of GABAergic neurons. We found, unexpectedly, that nRT cells are hyperpolarized by APV. This occurs because these cells have an unusual form of NMDAR (probably NR2C) that contributes inward current at resting potential in response to ambient glutamate. The hyperpolarization produced by APV is sufficient to deinactivate T-type calcium channels, and these trigger rhythmic bursting at delta frequency. The APV-induced delta frequency bursting is abolished by dopamine D2 receptor antagonist, indicating that dopamine and NMDAR antagonist work synergistically to stimulate delta frequency bursting. Our results have significant implications concerning the electrophysiological basis of schizophrenia and bring together the NMDAR hypofunction, dopamine, and GABA theories of the disease. Our results suggest that NMDAR hypofunction and dopamine work synergistically on the GABAergic cells of the nRT to generate the delta frequency EEG oscillations, a thalamocortical dysrhythmia (TCD) in the awake state that is an established abnormality in schizophrenia.